Analysis Of Calculation Of Cost Of Production Of Poached Egg Bakmi Using The Application Of The Full Costing Method In A Legiteat Noodle Business In Bengkulu City - Holiza, Nipa; Susanti, Neri; Hidayah, Nenden Restu (Tractare: Jurnal Ekonomi-Manajemen, 2024)
The aim of this research is to analyze the basic cost calculation analysis for the production of pouched egg noodles using the full costing method in the Legiteat Noodle Business in Bengkulu City. The analytical method used in this research is the descriptive method. The descriptive method is a form of research aimed at describing ongoing activities.The results of the study show that the calculation of the cost of production carried out by the Legiteat Noodle Business in Bengkulu City, the cost of production of pouched egg noodles per bowl is Rp. 7,705. Based on the full costing method, the cost of production of pouched egg noodles per bowl is Rp. 12,021. There is a difference in the calculation of the cost of production between the company's calculation and the full costing method. In the company method, the cost of raw materials and auxiliary materials is only calculated, while the full costing method makes a more detailed calculation by calculating all cost components, namely raw material costs, labor costs, factory overhead costs and non-production costs.